2014
DOI: 10.1186/1752-1947-8-18
|View full text |Cite
|
Sign up to set email alerts
|

Acute presentation of vasospastic angina induced by oral capecitabine: a case report

Abstract: IntroductionOral capecitabine is an oral prodrug of 5-fluorouracil that has been integrated into the management of multiple cancer types because of the convenience of administration and its efficacy compared with 5-fluorouracil. Capecitabine mimics the pharmacokinetics of intravenous 5-fluorouracil. While cardiac events associated with the use of 5-fluorouracil are a well-known side effect, capecitabine-induced cardiotoxicity has only been rarely reported.Case presentationWe present a case of a 46-year-old wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Golias et al reported a 46-year-old woman with gastric sarcoma who was administered cisplatin after capecitabine-induced cardiotoxicity. [2] In our case, we rechallenged capecitabine after 5-FU-induced cardiotoxicity. However, our patient still experienced chest pain with a high dose of capecitabine.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Golias et al reported a 46-year-old woman with gastric sarcoma who was administered cisplatin after capecitabine-induced cardiotoxicity. [2] In our case, we rechallenged capecitabine after 5-FU-induced cardiotoxicity. However, our patient still experienced chest pain with a high dose of capecitabine.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, fluoropyrimidine-induced cardiotoxicity is a rare but potentially serious toxicity. [2][3][4][5] The most common symptom of cardiotoxicity is anginal chest pain, and other symptoms include dyspnea and hypertension. Severe heart failure due to 5-FUinduced cardiotoxicity has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“… 17 , 18 As demonstrated in animal models and in human studies, 19 , 20 arterial vasospasm is one of the possible mechanisms of 5-FU related angina. During a capecitabine-related coronary spasm, patients may experience angina-like chest pain 21 , 22 and ventricular fibrillation. 23 , 24 Moreover, the diagnosis of vasospastic angina could be consistent with the hypothesis of an acute coronary syndrome also in the first cardiac event presented during neoadjuvant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing cardiac and renal diseases are reported risk factors for cardiotoxicity [11]. Capecitabine is enzymatically metabolized in the liver to 5-FU, which in turn plays a major role in inhibiting DNA and RNA syntheses in tumor cells by blocking the synthesis of precursor nucleotides [12]. In contrast to the direct myocardial toxicity of anthracyclines, capecitabine and its active metabolite 5-FU are thought to exert their cardiac effects by causing reversible coronary spasms [2].…”
Section: Discussionmentioning
confidence: 99%